Comparative analysis of students´ and professors´ satisfaction levels at the spanish public university - Martinez-Navalon, Juan-Gabriel; Blanco-González, Alicia; Del-Castillo-Feito, Cristina (Journal of Management and Business Education, 2019)
Public universities´ managers need to understand their stakeholders´ demands and needs. This task appears as a crucial aspect in order to have satisfied students and professors and to achieve the institution´s medium and long-term strategies. The aim of this paper is to analyze the satisfaction levels of both, students and professors in order to study possible improvements. For this purpose, a survey was distributed to students and professors of a Spanish public university and 756 responses were obtained. The results show that students and professors hold different satisfaction levels, which highlights the fact that internal and external stakeholders have diverse perceptions of the same institution. This information enhances the need of developing different strategies when managing the university´s satisfaction levels depending on the stakeholder group under consideration.